In Situ Fenestration Through the Contralateral Iliac Artery to Convert an Aortouni-iliac Into a Bifurcated Endograft. (June 2015) - Coscas, Raphaël; Glorion, Matthieu; Javerliat, Isabelle; Goëau-Brissonniere, Olivier; Coggia, Marc
Purpose: To present a technique of in situ fenestration that allows conversion of an aortouni-iliac endograft into a bifurcated endograft, thereby avoiding crossover femorofemoral bypass and its complications.Technique: Following conventional deployment of an aortouni-iliac endograft, in situ fenestration through the contralateral common iliac artery is performed with a transjugular intrahepatic access set. The fabric hole is enlarged using a cutting balloon and a high-pressure noncompliant balloon. Kissing iliac-covered stents are then positioned at the level of the bifurcation to convert the aortouni-iliac endograft into a bifurcated repair. To date, this technique has been successfully used in 4 patients with satisfactory short-term results.Conclusion: This technique represents another application of endograft in situ fenestration. This strategy provides a bifurcated repair in cases where bifurcated stent-grafts are usually precluded, such as a narrow distal aorta, ruptured abdominal aortic aneurysm, or combined aortoiliac occlusive disease.